Pathogenetic substantiation of a differential approach to the treatment of endometrial hyperplasia in women with abdominal obesity - Mokrianyn, Nataliia (Journal of Education, Health and Sport, 2025)
Background: Endometrial hyperplasia is a precursor to endometrial adenocarcinoma. According to the Global Cancer Observatory 2019, endometrial cancer affects 382,000 women worldwide per year. With timely detection and treatment of endometrial hyperplasia and modification of the factors that lead to excessive proliferation of the internal lining of the uterus, it will be possible to reduce the incidence and preserve the fertility of women of reproductive age. Excessive estrogen is the main cause of endometrial hyperplasia. While the leading mechanism of excessive endometrial proliferation is a disruption in the cyclical change in the ratio of production of the main female hormones estrogen/progesterone. Obesity is a pandemic of the 21st century. Abdominal obesity is the most metabolically dangerous variant of it, as it is characterized by distorted endocrine function, which disrupts the normal functioning of the hypothalamic-pituitary-ovarian system in women. and is also involved in impaired cellular sensitivity to insulin and low-grade chronic inflammation. Methods: This literature review summarizes the impact of abdominal obesity on the female reproductive system and explains the pathogenetic influence of abdominal obesity on the development, progression and recurrence of endometrial hyperplasia. Results: This review summarizes the importance of modern pathogenetic treatment of endometrial hyperplasia in women with abdominal obesity Conclusion:. It was found that the use of first-line drugs together with drugs that increase insulin sensitivity, lifestyle modification and the use of herbal remedies containing Vitex agnus castus can have a positive effect on the treatment of endometrial hyperplasia, and also report a positive effect on improving the quality of life and avoiding recurrence of the disease in women with abdominal obesity